Ethics Programs, Board Involvement, and Potential Conflicts of Interest in Corporate Governance - Felo, Andrew J. (Journal of business ethics, 2001)
Board composition, insider participation on compensation committees, and director compensation practices can potentially cause conflicts of interest between directors and shareholders. If these corporate governance structures result in situations where actions beneficial to directors do not also benefit shareholders, then shareholders may suffer., Corporate ethics programs usually address conflicts of interest that may arise in the firm's activities. Some boards of directors take active roles in their firms' ethics programs by actively overseeing the programs. This paper empirically examines the relationship between ethics programs and potential conflicts of interest and the relationship between board involvement in a firm's ethics program and potential conflicts of interest., Evidence in this paper shows that firms with ethics programs have a lower percentage of inside directors on their compensation committees than do firms without ethics programs. Firms in which boards are actively involved in the programs have more independent boards (higher percentage of independent directors and lower percentage of inside directors) and are more likely to compensate outside directors with equity than are firms in which boards are not actively involved in the programs. Supplemental analyses show that the incidence of potential conflicts of interest is not significantly different between firms without ethics programs and firms in which boards are not actively involved in the programs. Taken together, the evidence in this paper indicates that a board actively involved in an ethics program, and not the simple existence of an ethics program, is related to the incidence of potential conflicts of interest.